Rapid Gastric Emptying of an Oral Glucose Solution in Type 2 Diabetic Patients - Phillips, William T; Schwartz, Joyce G; McMahan, C. Alex (The Journal of nuclear medicine (1978), 1992)
Gastric emptying of a liquid glucose meal was measured with scintigraphic techniques in nine recently diagnosed Type 2 diabetic patients and nine sex- and age-matched nondiabetic control subjects. Seven of the nine Type 2 diabetic patients were receiving oral hypoglycemic therapy which was discontinued the evening prior to the study. The other two diabetic patients were taking no medication. The average gastric half-emptying time was 33.6 min (s.e.m. = 3.2) for the diabetic patients and 64.6 min (s.e.m. = 4.2) for the nondiabetic controls (p = 0.0005). These measurements indicate rapid gastric emptying in Type 2 diabetic patients which may contribute to worsening of glucose control in these patients.